Are governments able to lean against the macroeconomic wind? - David Kiefer (The University of Utah, Department of Economics, 2013)
A standard model of activist macroeconomic policy derives a monetary reaction rule by assuming that governments have performance objectives, but are constrained by an augmented Phillips curve. In addition to monetary policy governments apply a variety of instruments to influence inflation and output, including fiscal policy, bailouts and exchange rates. Solving the Phillips curve and reaction rule for a reduced form, we study this model with a panel of OECD countries. A textbook version of the activist model leads to implausible results. The econometric results are much enhanced by accounting for serial correlation among output shocks. Our results suggest that governments do lean against inflation shocks, but not output shocks, although the flatness of the Phillips curve limits policy makers' ability to effective lean against the wind. Furthermore, the activist model fits the data only slightly better than a flat-Phillips-curve benchmark. Some results are unexpected, like the estimated slope of the Phillips curves and the implied stabilization behavior of Finland, Japan and US policy makers.
Keywords: E61; E63; 330; stabilization policy; inflation targets; expectations